Age-related maculopathy and sunlight exposure evaluated by objective measurement. Issue 5 (25th April 2008) - Hirakawa, M; Tanaka, M; Tanaka, Y; Okubo, A; Koriyama, C; Tsuji, M; Akiba, S; Miyamoto, K; Hillebrand, G; Yamashita, T; Sakamoto, T
Abstract : Aim: To study the relationship between age-related maculopathy (ARM) and exposure to sunlight using an objective method. Methods: In a case–control study of Japanese men aged ⩾50 years (67 controls without ophthalmic disease and 148 with ARM), those with ARM were separated into groups of early (n = 75) and late (n = 73) ARM. Facial wrinkle length and area of hyperpigmentation, which are considered to be associated with exposure to sun, were measured using imaging with computer-based image analysis. Skin tone was also measured on the upper inner arm, which is not exposed to sun. Early and late ARM association with skin measurements was then evaluated. Results: Significantly more facial wrinkling (p = 0.047, odds ratio 3.8; 95% CI 1.01 to 13.97) and less facial hyperpigmentation (p = 0.035, odds ratio 0.3; 95% CI 0.08 to 0.92) was present in late ARM cases. The relationship between skin tone and ARM risk was not statistically significant. Conclusions: This objective method showed that lifetime exposure to sunlight is an important factor in the progression of late ARM. An individual's reaction to sunlight exposure may have a role in ARM progression in addition to total lifetime exposure to sunlight.